Tinjauan Mutu Biodiesel/Diesel Yang Beredar Di Lingkungan Spbu X Palembang - Abdul Hamid; Indah Agus Setiorini (Politeknik Akamigas Palembang, 2016)
Biodiesel/Diesel is the fuel types distillate brownish yellow clear, slightly more viscous than the kerosene, to stretch a boiling range between 180 370 ° C, is used as fuel for diesel engines high speed (greater than 1000 rpm) , such as public service vehicles, trucks, trailers, tools multiplier land, tractors, trains, etc. Biodiesel/Diesel is often referred to as gasoil, ADO (Automotive Diesel Oil) or HSD (High Speed Diesel Oil). This study aims to evaluate the quality Biodiedel/Diesel circulating whether qualified marketing especially designation automotive or diesel engines. Quality intended form of the results of testing several test parameters such as: Gravity (the specific gravity), the nature of Combustion (ignation quality), the nature of Evaporation (volatility), Flow properties (fluidity), the nature of Hygiene (cleanlines). The results of test diesel fuel from various stations in Seberang Ulu illustrates that the nature or characteristics of diesel fuel are researched generally still meets the specifications of both its use as fuel for diesel engines as well as the terms of the transaction and transport. Specific analysis of the results of Gravity is in the range from 0.820 to 0.870 which is 0.850 up to 0.852. Likewise, color analysis is under max 3.0 is 2,0 to 2,5. For Calculated Cetane Index where the average cetane index ranges from 47 until 48 is above specification (min 45). Evaporation nature can be seen from the distillation shows that the temperature FBP meet the specification is <370oC. Flow is determined by the nature of Pour Point between 35oF until 40oF Vs max 60oF while Viscosity 3.99 cSt until 4.00 Vs 1.6 cSt until 5.8 cSt.